The Protective Effect of Azelnidipine for the Prevention of Heart Fibrosis Occurrence on Balb/c Mice with Iron Overload - Sarosa, Hadi; Bahrudin, Udin; Soemantri, Ag; Muis, Siti Fatimah; Arfian, Nur; Hisatome, Ichiro (Bangladesh Journal of Medical Science, 2020)
Background: Iron overload can cause DNA oxidation which increase TGF β1, type 1 fibrilarprotein and myocardium fibrosis. Myocardium fibrosis is the main cause of death on the state of iron overload. The iron influx towards the cell during iron overload is still unknown, some research suggested LTCC acts as iron influx. This research aims to investigate the role of azelnidipine as type L calcium channel blocker, lowering TGF β1, collagen and myocardium fibrosis. Method: The research subjects consisted of 25 male Balb-C mice(8 weeks, 30-40mg) divided into 5 groups. Group 1 (NaCl+S) 0,3 cc Na Cl 0,9% (I.P) and drug solvent (Aquabidest, CMC and Nipagin) orally. Group 2Fe+S) 0.3 cc 1,5 mg Fe+sucrose (Venofer®) (I.P) and drug solvent (Aquabidest, CMC and Nipagin) orally. Group 3 (Fe+Dfx) 1,5 mg Fe+sucrose (Venofer®) (I.P) and deferasirox 20 mg/kg body weight/day orally, group 4 (Fe+Azl) 1,5 mg Fe+sucrose (Venofer®) (I.P) and azelnidipine 14 mg/day orally and group 5 (Fe+Dfx-Azl) 1,5 mg Fe+sucrose (Venofer®) (I.P) and mixture of deferasirox 20 mg/kg body weight/day and azelnidipine 14 mg/day orally. Fe-sucorse was diluted with NaCl 0.9 %. Intraperitoneal injection were administered intermittently for 60 days of treatment. Result: The highest Expression of TGF β, collagen I and fibrosis area fractions are in group Fe+S. The result of Post Hoc test between 2 treatment groups indicated that there were no difference in TGF β expression between groups NaCl+S with Fe+Dfx (P>0.05) , Fe+Dzl (P>0.05). There are no significant in collagen expression between groups NaCl+S with Fe+Dfx (P > 0.05) ,Fe+Dzl (P>0.05). Conclusion: Azelnidipine, LTCC have roles on the influx of iron into the myocardium, lowering TGF β, collagen Iexpressionsand myocardium fibrosis. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.223-228